Performance Assessment and Mechanical Behavior of Bamboo/Sisal/Chopped Mat Fiber Hybrid Composites Prepared by Hand Lay-Up Process - SSS Lokesh; Konijeti Sri Manikanta (Utilitas Mathematica, 2025)
The rising demand for sustainable and lightweight materials has accelerated research into natural fiber-reinforced composites as eco-friendly alternatives to synthetic systems. In this work, bamboo, sisal, and chopped strand mat (CSM) fibers were combined in an epoxy matrix using the hand lay-up technique. Seven composite configurations were fabricated and evaluated according to ASTM standards for tensile, flexural, impact, and hardness properties. Among them, the bamboo/sisal/CSM hybrid composite demonstrated superior performance, achieving tensile strength of 98.2 ± 4.9 MPa, flexural strength of 173.3 ± 6.8 MPa, impact energy of 5.75 ± 0.35 J, and Brinell hardness of 76.3 ± 2.1. The enhanced performance was attributed to the complementary roles of the reinforcing fibers: bamboo imparting stiffness, sisal contributing ductility, and CSM improving isotropy and hardness. Comparative assessment with recent literature (2020–2025) revealed consistent trends, confirming the structural reliability and sustainability of such hybrid composites. Overall, the study highlights the potential of bamboo/sisal/CSM composites as viable alternatives for automotive, aerospace, and construction applications, aligning with circular economy principles while advancing engineering innovation and environmental responsibility.